Medullary Thyroid Carcinoma with Micronodular Lung Metastases: A Case Report with an Emphasis on the Imaging Findings. (5th May 2010) - Ventura, Nina; Marchiori, Edson; Zanetti, Gláucia; Muccillo, Antonio; Pereira, Mariana Leite; Abdalla, Guilherme; Martins, Pedro; Constantino, Carolina Lamas; Canellas, Rodrigo; Brandão, Viviane; Varella de Oliveira, Romulo
Abstract : Medullary thyroid carcinoma is a rare malignancy that arises from calcitonin-producing C-cells and frequently metastasizes to lymph nodes in the neck. Distant metastases may involve bone, lung, and liver. The infrequent number of cases limits the clinical nature and ability to optimize diagnostic tools. Here, we present a case of a micronodular radiographic pattern in metastatic medullary thyroid cancer in order to enhance awareness of the disease process. A case discussion and relevant review of the literature are provided.